Robust scalable synthesis of surfactant-free thermoelectric metal chalcogenide nanostructures. (July 2015) - Han, Chao; Li, Zhen; Lu, Gao Qing (Max); Xue Dou, Shi
Abstract: A robust low-cost ambient aqueous method for the scalable synthesis of surfactant-free nanostructured metal chalcogenides (M a X b, M=Cu, Ag, Sn, Pb, and Bi; X=S, Se, and Te; a =1 or 2; and b =1 or 3) is developed in this work. The effects of reaction parameters, such as precursor concentration, ratio of precursors, and amount of reducing agent, on the composition, size, and shape of the resultant nanostructures have been comprehensively investigated. This environmentally friendly approach is capable of producing metal chalcogenide nanostructures in a one-pot reaction on a large scale, which were investigated for their thermoelectric properties towards conversion of waste heat into electricity. The results demonstrate that the thermoelectric properties of these metal chalcogenide nanostructures are strongly dependent on the types of metal chalcogenides, and their figure of merits are comparable with previously reported figures for their bulk or nanostructured counterparts. Graphical abstract: Highlights: Ambient scalable synthesis of surfactant-free thermoelectric metal chalcogenide nanostructures. Low cost and environmental friendly aqueous approach. Extremely low solubility and in-situ release of hydrogen lead to small nanostructures. Enhanced and comparable thermoelectric properties with bulk and nanoscale analogs fabricated from complex methods.